EDUCATION MANAGEMENT: INITIAL NOTES ON THE IMPLEMENTATION OF THE ARTICULATED ACTION PLAN IN ALTAMIRA-PA - Sousa, Raimundo (Revista Gênero e Interdisciplinaridade, 2026)
This text describes and analyzes the initial process of construction of the Articulated Action Plan (PAR) of the Municipality of Altamira-PA, having as reference, the year 2007. In 2007, Brazilian municipalities were mobilized, in the context of the launch of the Education Development Plan (PDE) by the Federal Government, to adhere to the All for Education Commitment Goal Plan. Based on theoretical references, legislation and official documents of the MEC/FNDE and SEMED of Altamira-PA, a brief analysis of the process of implementation of the PAR was elaborated. The management process of construction and implementation of the PAR followed the guidelines of MEC consultants and manuals on the PAR policy, which can characterize a strong centralism of the Union.